USE OF UAV AND GIS FOR ERODED SOIL CALCULATION ON A GULLY LOCATED IN THE AMADEU AMARAL DISTRICT, IN MARILIA, SP - BRAZIL - Julian, Carolina [UNESP]; Rodrigues Nunes, Joao Osvaldo [UNESP] (Uniao Geomorfologia Brasileira, 2020)
Soil is an essential natural resource for food production, which is directly affected for this degradation, whereby erosion is one of the main associated causes, which quantification are still being studied, due to the complexity of the erosion process. GIS tools are used as a form of analysis, in which the Unmanned Aerial Vehicle (UAV) has stood out for its high efficiency and relatively low cost. Considering this, this article aims to estimate the soil eroded in a gully located in the district of Amadeu Amaral, Marilia / SP - Brazil. The erosion volume was calculated using data from the aerial survey with UAV and GIS tools from the QGis software. It was estimated that about 19,664.61 m(3) of soil, approximately 34,806.35 t, were lost due to gullying, a result that, despite errors inherent to the methodology employed, presents an order of magnitude for the amount of eroded soil. Therefore, in addition to this estimate, the methodology showed the possibility of being used to monitor the area, which would enable a better understanding of these processes and obtain prediction models for these erosions.
Keywords: Gully volume; GIS; Soil erosion